(untitled) (American Journal of Business Management, Economics and Banking, 2023)
Many studies in the last three decades have focused on public debt management, known as financial sustainability, as public debt is considered financially sustainable if it fulfills the condition of the ability to pay the debt (solvency condition fiscal). For this condition to be fulfilled there must be a primary surplus in the budget sufficient to pay off this debt, whether it’s essential value or the benefits accruing from it; that is, this condition requires that the volume of the current deficit, in addition to the current discounted value of spending, not exceed the present value of the return. In other words, the present value of the debt should be greater than the current discounted value of the total revenues minus the non-interest spending.